2013
DOI: 10.1111/geoj.12033
|View full text |Cite
|
Sign up to set email alerts
|

Interacting forms of expertise and authority in mega‐event security: the example of the 2010 Vancouver Olympic Games

Abstract: This paper explores the interests, forms of expertise and sources of authority in security governance at the 2010 Vancouver Olympic Games. To do so, the research approach pursued here focuses on the micro level, locating the various contributions to event security in the context of a particular range of projects and decisions relating to the planning and instauration of Olympic venue security. On this basis, the paper empirically explores how security governance at sport mega events, as the outcome of complex … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(7 citation statements)
references
References 14 publications
0
7
0
Order By: Relevance
“…Only one author has suggested that joint staffing among organizations positively influences the development of interagency collaboration. 33 These liaison roles managed to create shared meanings among organizations while maintaining interoperable communication systems among them.…”
Section: Discussionmentioning
confidence: 99%
“…Only one author has suggested that joint staffing among organizations positively influences the development of interagency collaboration. 33 These liaison roles managed to create shared meanings among organizations while maintaining interoperable communication systems among them.…”
Section: Discussionmentioning
confidence: 99%
“…The relationships that these teams have built with one another help them in moments of conflict to remember that everyone is trying to do the best for the client and the guests (Klauser, 2015). Keeping the end goal in mind helps eliminate personal feelings of team conflict and drive the conversation forward.…”
Section: Resultsmentioning
confidence: 99%
“…Large event security has become increasingly complicated over the past 20 years. Megaevents consistently contribute to local economic development in a positive way but also attract much attention concerning security-related issues involving all the stakeholders (Amorin et al, 2014;Boyle & Haggerty, 2009;DiSalvatore, 2019;Klauser, 2015). Security cases have included the headline tragedies such as the Las Vegas shooting in 2017 and the Boston Marathon bombing of 2013.…”
Section: Introductionmentioning
confidence: 99%
“…However, as Whelan (2014) argues, coordination becomes increasingly tricky in an SME setting, where the security performance and deliveries are under the scrutiny of the watchful eye of the public. Moreover, inter-organizational tensions between law enforcements, security agencies and professionals with responsibilities for security, actors' own interests and rules of engagement may add to this (Boyle et al, 2015;Fussey, 2015;Klauser, 2015;Taylor & Toohey, 2015;Whelan & Molnar, 2019). 7 Collaboration between actors simply cannot be achieved by establishing a network (Whelan, 2016), whilst cooperation does not automatically translate into trust between actors within the network (Klauser, 2015;Whelan, 2015).…”
Section: International Collaboration and Security Network At Mega-evmentioning
confidence: 99%